Teknik Guru dalam Mendongeng Cerita Rakyat pada Pembelajaran Tematik Muatan Bahasa Indonesia Siswa Kelas II SDN 101 Kota Bengkulu - Juliansyah, Wilky Putra; Muktadir, Abdul; Dalifa (Universitas Bengkulu, 2024)
This study aims to describe the teacher's technique in storytelling folklore in the thematic learning of Indonesian language content for class II students at SDN 101 Bengkulu city. This type of research is a qualitative research with descriptive research methods. The subject of this research is the principal of SDN 101 Bengkulu city. Data collection techniques using observation, interviews, and documentation. Data analysis techniques were carried out by collecting data, reducing data, presenting data, and drawing conclusions. Data validity uses technical triangulation and member checks. The teacher's technique in telling folklore consists of sound techniques and body techniques. The sound technique used by the storyteller, namely the teacher in telling folklore in the thematic learning of Indonesian language content for class II students at SDN 101 Bengkulu city, can be said to be in accordance with the storytelling technique. An understanding of sound techniques is very important to learn so that storytellers can perform and understand processing breathing, processing vocals, intonation and also tempo in storytelling. If this sound technique is implemented properly by all teachers, there will be no more students who do not understand storytelling. The body technique used by the storyteller, namely the teacher in telling folklore in the thematic learning of Indonesian language content, class II students at SDN 101 Bengkulu city is able to understand and have body techniques which include concentration, gestures or body movements and also blocking. So with this it is important for every storyteller to understand and implement body techniques in elementary schools.